Preoperative Progressive Pneumoperitoneum in the Treatment of Hernias With Loss of Domain. Our Experience in 50 Cases - Helena Subirana; Jaume Comas; Oriol Crusellas; Joaquim Robres; Joan Barri; Ana Domenech; Cristina Borlado; Jordi Castellví (Journal of Abdominal Wall Surgery)
Introduction: Surgical planning for repair of giant hernias with loss of domain needs to consider patient comorbidities, potential risks and possible postoperative complications. Some postoperative complications are related to the increase in intra-abdominal pressure caused by the reintroduction of abdominal contents into the peritoneal space. Preoperative progressive pneumoperitoneum (PPP) increases the capacity of abdominal cavity prior to hernia repair and allows for better physiological postoperative adaptation. The aim of this study is to analyze perioperative and intraoperative characteristics as well as outcomes of a cohort of patients treated with PPP prior to giant hernia repair at a single, high volume center.Methods: Prospective, descriptive, observational single-center study including 50 patients undergoing PPP prior to hernia with loss of domain repair between January 2005 and June 2022. We analysed epidemiological, surgical and safety variables.Results: Fifty patients were included: 43 incisional hernias, 6 inguinal hernias and 1 umbilical hernia. Mean age was 66 years (36–85). Median insufflation time was 12 days (4–20) and median insufflated volume of ambient air was 10,036 cc. There were complications during PPP in nine patients: 2 decompensation of chronic respiratory disease and 7 subcutaneous emphysema. PPP was prematurely suspended in patients with respiratory decompensation. All patients with incisional and umbilical hernias underwent open repair with mesh placement. Preperitoneal repair was performed in inguinal hernias. Three cases of hernia recurrence were reported during the follow up.Conclusion: PPP is a safe and effective tool in the preoperative management of patients with giant hernias. It helps to achieve the decrease or absence of abdominal wall tension and can favour the results of complex eventroplasty techniques.